2015
DOI: 10.1080/15376494.2012.761302
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Failure Analysis of Laminated Composite Plates With Two Serial Pinned Joints

Abstract: This study presents experimental and numerical failure analyses for two serial pin loaded holes in unidirectional carbon fiber/epoxy resin composite laminates. The failure loads and failure modes of composite laminates are determined for different geometrical parameters and different stacking sequences. Three-dimensional ANSYS Parametric Design Language codes are developed in the ANSYS R finite element software. Hashin Failure Criteria and material degradation rules are used to determine failure loads and fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…In the experimental loading, bearing failure occurred in the specimens. For this reason, a partial decrease in the load after the first maximum load followed by a constant trend occurred [32]. Force-displacement plots show sudden damage, rupture, or separation damage that occurs without or shortly after a significant descent [24].…”
Section: Comparison Of Experimental and Numerical Resultsmentioning
confidence: 99%
“…In the experimental loading, bearing failure occurred in the specimens. For this reason, a partial decrease in the load after the first maximum load followed by a constant trend occurred [32]. Force-displacement plots show sudden damage, rupture, or separation damage that occurs without or shortly after a significant descent [24].…”
Section: Comparison Of Experimental and Numerical Resultsmentioning
confidence: 99%
“…The type of failure is changed with the increase of the M/D ratio as bearing for first pin. 24 First, failure starts from first pin (Figure 3). This situation appears as a sudden drop in linear zone of load-displacement graphs.…”
Section: Resultsmentioning
confidence: 99%
“…The dimensions of the specimens used in the tensile tests performed to determine the pin-joint behavior of glass fiber epoxy composite materials are shown in Figure 3. Detailed dimensions of pin-joint test apparatus in Figure 3 can be taken from Turan et al 23,24 The circular hole diameter (D) is 6 mm. The distance between the pin center and the plate free edge (E) and the distance between the two pins (M) values with their coding name are given in Table 2.…”
Section: Definition Of the Problem And Experimentsmentioning
confidence: 99%
“…It was also shown that conventional point stress criterion cannot be adopted under certain circumstances. Turan et al [ 14 ] investigated the failure loads of composite laminates including two serial pin‐loaded holes in unidirectional carbon fiber reinforced composite laminates for different stacking sequences. The bearing failure was happened while the distance between the holes was 2.5 times higher than the diameter of the holes, whiles for lower ratios the shear‐out failure occurred.…”
Section: Introductionmentioning
confidence: 99%